Pemberdayaan Inovasi LORALI dalam Pengembangan Ekoenzim di Pesantren Baitul Arqam, Aceh Besar - Suwarniati Suwarniati; Qurratu Aini; Meutia Zahara; Rosnidarwati Rosnidarwati (I-Com: Indonesian Community Journal, 2024)
This community service program aims to re-use Eco-Friendly Organic Waste (LORALI) for the production of eco-enzyme. The program begins with a socialization session on the benefits of eco-enzyme, the techniques for making it, and its derivative products, targeted at both the pasantren (Islamic boarding school) management and its students. It is hoped that the partners will be able to manage organic waste independently, reduce environmental pollution, and enhance students' skills in eco-enzyme production and entrepreneurship, ultimately contributing to economic improvement. The results indicate that students’ knowledge and skills in eco-enzyme production have increased, as evidenced by high-quality, contamination-free products produced during the program.